The effect of financial inclusion on bank stability: Evidence from ASEAN - Nguyen Duc Trung; Quynh Lan Thi Du (Cogent Economics & Finance, 2022)
After the recent global financial crisis of 2008, the attention of researchers and politicians has focused on both financial inclusion and bank stability. However, we still know little of how the former impacts the stability of financial services providers. This paper focuses on financial inclusion and its influence on bank stability. By using a sample of 102 banks in six countries of ASEAN over the period 2008-19, we achieve the result that the index of financial inclusion has a positive relationship with Zscore and a negative effect on the standard deviation of deposit growth rates and nonperforming loan ratio, which also means that higher level of financial inclusion contributes to greater bank stability. Or, to make it clearer, in an inclusive financial sector, those banks can increase more stable customer deposits and safe loans by providing banking services. The indices calculated for each dimension of financial inclusion, including accessibility, availability, and usage of the formal bank system, also have the same results. Our findings have important policy implications that ASEAN policymakers do not have to face a tradeoff between focusing on reforms to promote financial inclusion and focusing on further improvements in bank stability.
Keywords: G18; G21; G28; F65; 330; financial inclusion; bank stability